Clinical and angiographic outcomes of true vs. false lumen stenting of coronary chronic total occlusions: Insights from intravascular ultrasound. Issue 3 (22nd October 2018) - Sabbah, Mahmoud; Tada, Takeshi; Kadota, Kazushige; Kubo, Shunsuke; Otsuru, Suguru; Hasegawa, Daiji; Habara, Seiji; Tanaka, Hiroyuki; Fuku, Yasushi; Goto, Tsuyoshi
Abstract: Objectives: The clinical implications of subintimal stenting (SS) of the recanalized chronic total occlusion (CTO) segment have not been characterized. We evaluated the in‐hospital and the long‐term clinical and angiographic outcomes of drug‐eluting stents (DESs) deployed in true vs. false lumen of successfully recanalized CTO. Methods and results: Two independent reviewers analyzed the intravascular ultrasound (IVUS) images of 173 successfully recanalized CTO lesions (157 patients), between August 2011 and October 2012. After successful guidewire (GW) crossing, lesions were classified according to IVUS evaluation into two groups: (1) true lumen (TL) stenting group and (2) SS group; and compared with regards to in‐hospital and long‐term clinical outcomes. In 154 lesions, DESs were deployed in the TL; and in 19 (11%) lesions, DESs were deployed in the subintimal space (95% confidence interval: 6.3–15.6%). False GW tracking in the SS group resulted in increased rates of IVUS‐detected dissection flaps (84% vs. 42.6%, P ≤ 0.001), intramural hematoma (32 vs. 11%, P = 0.01), and minor perforations 6/19 (31.6% vs. 8.4%, P = 0.002). At 1‐year follow‐up, both groups had similar cumulative rates of binary restenosis and target lesion revascularization ( P = 0.73 and P = 0.97, respectively). Six patients (4.6%, 6/129 patients) in the TL group and none in the subintimal group died at 1 year. Conclusions: Acknowledging some limitations, our observations may suggest that, subintimal stent deployment in a recanalized CTO segments, using second generation DES and IVUS guidance, might have a comparable success rate and long‐term angiographic and clinical outcomes as TL stenting.